The Interactive Role of Cognitive Diversity in The Relationship Between Enlightened Leadership and Perseverance Behaviors at Work : A Survey Study of The Opinions of a Group of Employees at Kala Dairy Products Company - Majeed Al Nasrawe, Adil (Iraqi Journal for Administrative Sciences, 2026)
The main objective of the study is to test the fundamental role that cognitive diversity plays in interacting with the relationship between enlightened leadership and its impact on the persistence behavior of employees. Using the most common scientific method, which is the descriptive analytical method, in order to diagnose the relationship between the study variables with greater accuracy. To collect information and data about the study problem, the questionnaire was used as a basic tool. The study targeted individuals working in the Kala Dairy Products Company in Karbala. The number of questionnaires distributed to the working individuals was (98) questionnaires, and the statistical data were analyzed through the statistical program (SPSS, AMOS. V23), as the PEARSON correlation coefficient was used, and for the influence relationships, the structural equation modeling was used. One of the most important conclusions reached is that enlightened leadership has a strong and effective impact on promoting perseverance behavior, and that cognitive diversity plays an effective role in strengthening this relationship, which increases their dedication and commitment to work.